Early Social Environment Affects the Endogenous Oxytocin System: A Review and Future Directions - Alves, Emily; Fielder, Andrea; Ghabriel, Nerelle; Sawyer, Michael; Buisman-Pijlman, Femke T. A. (Frontiers in Endocrinology, 2015)
Endogenous oxytocin plays an important role in a wide range of human functions including birth, milk ejection during lactation and facilitation of social interaction. There is increasing evidence that both variations in the oxytocin receptor (OXTR) and concentrations of oxytocin are associated with differences in these functions. The causes for the differences that have been observed in tonic and stimulated oxytocin release remain unclear. Previous reviews have suggested that across the life course, these differences may be due to individual factors, e.g. genetic variation (of the OXTR), age or sex, or be the result of early environmental influences such as social experiences, stress or trauma partly by inducing epigenetic changes. This review has three aims. First, we briefly discuss the endogenous oxytocin system, including physiology, development, individual differences and function. Secondly, current models describing the relationship between the early life environment and the development of the oxytocin system in humans and animals are discussed. Finally, we describe research designs that can be used to investigate the effects of the early environment on the oxytocin system, identifying specific areas of research that need further attention.